Cytotoxicity and Antibacterial Activity of Silver Complexes Bearing Semicarbazones and Triphenylphosphine - Almeida, Vitor Y. G.; Rocha, Josias S.; Felix, Débora P.; Oliveira, Gabriela P.; Lima, Mauro A.; Farias, Renan L. [UNESP]; Zanetti, Renan D. [UNESP]; Netto, Adelino V. G. [UNESP]; Zambom, Carolina R. [UNESP]; Garrido, Saulo S. [UNESP]; Rocha, Fillipe V. (Wiley, 2020)
The present work aimed to evaluate the biological activities of the silver (I) complexes, with the formulae [Ag(L)(PPh3)2]+ and [Ag(L)2]+ (L=(E)-2-((E)-3-phenylallylidene) hydrazine-1-carboxamide – CSC and (2E)-2-[(3E)-4-phenylbut-3-en-2-ylidene]-hydrazinecarboxamide – BSC). Four new silver(I) compounds were synthesized and characterized by NMR 1H, 13C-{1H}, 31P, IR, and UV-Vis spectroscopies, molar conductivity, and elemental analysis (CNH). High cytotoxicity was found for all complexes being more active than cisplatin in the tested cell lines. The antibacterial assay demonstrated that the compounds without phosphine groups presented high levels of inhibition (80 %) at 70.4 uM against the Gram-positive and Gram-negative bacteria strains. The DNA interactions were investigated by UV-Vis DNA titration, electrophoresis, and circular dichroism experiments. Data showed that the compounds did not interact with DNA in the tested conditions. However, the compounds have provided important information about the structural features that are needed in order to design new silver (I) complexes with biological activities.
Keywords: Antibacterial; Antiproliferation; DNA interaction; NMR spectroscopy; Silver (I)